2007
DOI: 10.1007/s11103-007-9211-6
|View full text |Cite
|
Sign up to set email alerts
|

Flowering of strict photoperiodic Nicotiana varieties in non-inductive conditions by transgenic approaches

Abstract: The genus Nicotiana contains species and varieties that respond differently to photoperiod for flowering time control as day-neutral, short-day and long-day plants. In classical photoperiodism studies, these varieties have been widely used to analyse the physiological nature for floral induction by day length. Since key regulators for flowering time control by day length have been identified in Arabidopsis thaliana by molecular genetic studies, it was intriguing to analyse how closely related plants in the Nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
3
38
0
1
Order By: Relevance
“…3, A-C). Additional evidence obtained through functional studies in other distantly related species indicates that the role of the FUL/SHP network in fruit dehiscence and lignification is widely conserved, at least in dicot plants (Smykal et al, 2007;Fourquin and Ferrándiz, 2012;Pabón-Mora et al, 2012).…”
Section: Coiled Pod Morphology In Medicago Genus Correlates With Stromentioning
confidence: 95%
“…3, A-C). Additional evidence obtained through functional studies in other distantly related species indicates that the role of the FUL/SHP network in fruit dehiscence and lignification is widely conserved, at least in dicot plants (Smykal et al, 2007;Fourquin and Ferrándiz, 2012;Pabón-Mora et al, 2012).…”
Section: Coiled Pod Morphology In Medicago Genus Correlates With Stromentioning
confidence: 95%
“…FUL plays a role in maintaining proper carpel wall growth during fruit development in Arabidopsis, and experiments overexpressing the euFUL gene DEFH28 from snapdragon in Arabidopsis (Mü ller et al, 2001) or silencing euFUL copies such as VmTR4 from bilberry (Vaccinium myrtillus; Jaakola et al, 2010) and Solanum lycopersicum MADS-box protein7 (SlMBP7) from tomato (R. Meyer, N. Pabó nMora, and A. Litt, unpublished data) suggest that other euFUL genes also play a role in fruit development. We have shown that FUL-like genes in Papaveraceae also play a role in proper fruit development similar to that of FUL and other euFUL genes, including ectopic lignification of the mesocarp (Gu et al, 1998;Mü ller et al, 2001;Smykal et al, 2007;Jaakola et al, 2010); this and other abnormalities could be responsible for premature rupture of the fruit wall. Thus, our data from Papaveraceae show that their FUL-like genes (1) function in proper floral meristem and sepal identity, similar to AP1 and other euAP1 genes, and (2) are required for proper fruit wall growth and cell differentiation, similar to euFUL genes.…”
Section: Ful-like Genes Function Pleiotropically During Plant Developmentioning
confidence: 95%
“…In petunia (Petunia hybrida), silencing of PETUNIA FLOWERING GENE (PFG) resulted in plants that remained vegetative (Immink et al, 1999). Overexpression of an Antirrhinum euFUL paralog, DEFICIENS-homolog28 (DEFH28), in Arabidopsis (Mü ller et al, 2001) and of the Nicotiana tabacum FUL (NtFUL) in tobacco (Nicotiana tabacum; Smykal et al, 2007) resulted in fruits with defective lignification that failed to dehisce. These data suggest that other euFUL genes may have the same dual roles as FUL: an early role in promoting the transition to reproductive meristems and a late role in proper fruit development.…”
mentioning
confidence: 99%
“…We observed higher and lower transcript levels in the overexpressor and suppressor lines, respectively, for N. sylvestris MADS1 and MADS2 as well as a decrease of NFL2 in the suppressor line. NsMADS1 and NsMADS2 belong to the SQUAMOSA subfamily of floral meristem and organ identity proteins, including Arabidopsis APETALA1 (AP1; Becker and Theissen, 2003;Smykal et al, 2007). NsMADS1 is an ortholog to the floral transition marker NtMADS11 (Jang et al, 2002;Gallego-Giraldo et al, 2007).…”
Section: Redox Modulation Of Boltingmentioning
confidence: 99%
“…AOX, Alternative oxidase; EFD, EF-hand domain; Etio., etiolated; Fl., flower; Mat., mature; Src., source; UCP, uncoupling protein. scriptionally induced in the stem apex during floral transition (Cho et al, 1999;Jang et al, 1999;Smykal et al, 2007). Thus, NsMADS2 has a central function for bolting and flowering induction in N. sylvestris, possibly similar to AP1 in Arabidopsis (He and Amasino, 2005).…”
Section: Redox Modulation Of Boltingmentioning
confidence: 99%